A Translational Approach to Clinical Data and Molecular Profiling in Ovarian Cancer - McNevin, Ciara (Trinity College Dublin. School of Medicine. Discipline of Histopathology, 2026)
Ovarian cancer (OC) remains one of the most lethal gynaecological malignancies, characterised by late-stage presentation, intrinsic genomic instability, and frequent development of treatment resistance. Although the identification of cancer-predisposing genetic alterations (CPGAs) such as BRCA1 and BRCA2 has transformed therapeutic strategies, significant challenges persist in linking molecular mechanisms of resistance to clinical outcomes. In this thesis, we investigated the genomic and transcriptomic determinants of hereditary and treatment-resistant OC and developed the foundational infrastructure to support genomic research in Ireland. Our integrated approach combined clinical cohort analysis, in vitro modelling, and registry-based data collection to bridge translational and real-world insights. We first characterised the prevalence and clinical implications of BRCA1 and BRCA2 pathogenic variants in Irish OC cohorts using paired germline and somatic testing data. We demonstrated the feasibility and clinical value of unified testing across Irish cancer centres, providing the first national dataset describing BRCA1/2-associated OC. These findings informed ongoing national policy development in genomic medicine. We then developed chemotherapy- and PARP inhibitor (PARPi)-resistant OC cell line models across BRCA1-mutant, BRCA2-mutant, and BRCA-wildtype backgrounds through stepwise drug exposure reflecting clinically relevant plasma concentrations. Using circRNA and miRNA profiling, we identified over 4,000 differentially expressed circRNAs and prioritised five circRNA candidates (hsa_circ_400223, hsa_circ_003300, hsa_circ_008026, hsa_circ_100059, and hsa_circ_025636) for validation. Functional enrichment analysis revealed dysregulation of DNA repair, chromatin organisation, and intracellular signalling pathways, implicating these non-coding RNAs in mechanisms of acquired chemoresistance. We further identified miRNA regulators differentially expressed by BRCA status, including miR-27b-3p, miR-205-5p, and miR-590-3p, suggesting potential utility as molecular signatures of tumour phenotype and therapeutic response. Validation across cell line models and clinical samples confirmed the expression trends of selected circRNA candidates, providing proof-of-concept for their biomarker potential. In parallel, we devised and implemented the CAmPaiGn pilot registry—the first Irish registry for individuals with CPGAs—establishing a framework for structured data collection across demographic, clinical, and genomic domains. Through national survey work and direct patient and public involvement (PPI), we demonstrated strong public willingness to contribute data for research and clinical integration, underscoring feasibility for a future national hereditary cancer registry. Collectively, this work provides new molecular insights into mechanisms of resistance in BRCA-mutant OC, identifies circRNA and miRNA candidates with biomarker potential, and establishes the infrastructure required to translate these findings into clinical practice. By combining in silico, in vitro, and clinical methodologies, we demonstrated how molecular discovery can inform predictive, personalised cancer care and shape the future of precision oncology in Ireland.
APPROVED
Keywords: circular RNA; circRNA; registry; BRCA; Ovarian Cancer